2003 46th Midwest Symposium on Circuits and Systems
DOI: 10.1109/mwscas.2003.1562405
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of three encryption/decryption algoriithms

Abstract: This paper presents an implementation of three encryption algorithms and a comparison between them based on CPU execution time. The CPU execution time is broken down to kernel and user time. The selected algorithms are: DES, Triple-DES (T-DES) and Blowfish. These are symmetric block encryption algorithms. The objective of this research is to evaluate the performance of the three cryptography algorithms in terms of the processing time required in the kernel and user space for generating the secret key, encrypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…DES is type of block cipher which works on 64 bits at a time. Some research has been proposed in this area of DES using discrete wavelet transform (DWT) which combines encryption as well as compression (Kofahi et al, 2003). The timing measurements, however, show that software of compression and encryption scheme may not be that much efficient to encrypt video stream in real time because this algorithm uses only one key to encrypt as well as decrypt the data (Dang and Chau, 2000).…”
Section: Related Workmentioning
confidence: 99%
“…DES is type of block cipher which works on 64 bits at a time. Some research has been proposed in this area of DES using discrete wavelet transform (DWT) which combines encryption as well as compression (Kofahi et al, 2003). The timing measurements, however, show that software of compression and encryption scheme may not be that much efficient to encrypt video stream in real time because this algorithm uses only one key to encrypt as well as decrypt the data (Dang and Chau, 2000).…”
Section: Related Workmentioning
confidence: 99%
“…From the experiment it was concluded that AES is not energy efficient for performing encryption and decryption on a file as RC4. In paper [11], the author compared the three symmetric key cryptographic algorithms Blowfish and DES. In paper [9], the author has compared the three symmetric key cryptographic algorithms Blowfish, DES and AES for different block cipher modes, like ECB, OFB and CBC.…”
Section: Data Encryption Algorithms For Pcementioning
confidence: 99%
“…In light of the investigations, it has been reasoned that the Blow-fish is the topmost performing calculation on the calculations decided for usage. The authors in [9] exhibit a usage of 3 encryption-calculations and a correlation through them in light of CPUexecution-time. The CPU-execution-time is separated to bit and client-time.…”
Section: Motivationmentioning
confidence: 99%